Osmotic Demyelinating Syndrome - G. R. Ramazanov; E. V. Shevchenko; E. A. Kovaleva; I. G. Zhelev; V. N. Stepanov; S. Z. Shakhpazov; K. V. Korigova; S. S. Petrikov (Неотложная медицинская помощь)
ABSTRACT. This article discusses the clinical cases of rare and difficult to diagnose brain damage — osmotic demyelinating syndrome (ODS). ODS is a lifethreatening condition, manifested by acute demyelination of the headbrain on the background of water-electrolyte disturbances,usually associated with fast management of hyponatremia. Within the framework of ODS, central pontine myelinolysis (CPM) and extra-pontine myelinolysis (EPM) are observed, which are accompanied by acute demyelination in the pons and white matter of the cerebral hemispheres, respectively. In 60%, CPM combine with EPM. The main reason for the development of ODS is a violation of water-electrolyte metabolism associated with alcohol abuse, chronic hepatic and/or renal failure, diabetes mellitus, Sheehan syndrome, polydipsia, condition after the removal of pituitary adenoma, bulimia, immunodeficiency syndrome. Today, the diagnosis of ODS is based on magnetic resonance imaging of the brain. The article indicates the main causes of the disease, clinical features, methods of diagnosis and treatment, as well as the outcomes of the disease.